2020
DOI: 10.1002/vms3.266
|View full text |Cite
|
Sign up to set email alerts
|

Methadone does not potentiate the effect of doxorubicin in canine tumour cell lines

Abstract: Opioid receptor activation was shown to enhance the efficacy of anti‐neoplastic drugs in several human cancer cell lines. In these cell lines, doxorubicin increased the number of opioid receptors and methadone concurrently enhanced cellular doxorubicin uptake. Triggered through lay press and media, animal owners started to challenge veterinary oncologists with questions about methadone use in anti‐cancer therapy. Especially in veterinary medicine, where side effects of chemotherapy are tolerated to a lesser ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…We have previously shown that P-gp is not expressed in U87, U251 and U373 cell lines [18] which might explain why these cells could not be sensitized to doxorubicin by MET, while inhibition of doxorubicin e ux has previously been reported for the A172 cell line [10]. Our ndings are in line with a study which also reported no sensitizing effect of MET on various doxorubicintreated canine tumor cells [12].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have previously shown that P-gp is not expressed in U87, U251 and U373 cell lines [18] which might explain why these cells could not be sensitized to doxorubicin by MET, while inhibition of doxorubicin e ux has previously been reported for the A172 cell line [10]. Our ndings are in line with a study which also reported no sensitizing effect of MET on various doxorubicintreated canine tumor cells [12].…”
Section: Discussionsupporting
confidence: 89%
“…In a tumor model of nude mice implanted with U87 GBM cells, MET treatment reduced tumor growth and volume [9]. On the other hand, more recent data indicate no sensitizing effect of MET on various doxorubicin-treated canine tumor cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin is frequently used in veterinary medicine; thus, the question arose whether MTD is useful also for increasing the effectiveness of therapy of animals. In a recent study with µ-receptor expressing canine cell lines, authors did not observe a potentiation of doxorubicin-induced growth inhibition by MTD and, overall, were unable to confirm the data summarized above [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism of action rests on activation of MOR, inhibition of P-gp by MET leading to increased intracellular doxorubicin levels, and subsequent induction of apoptosis (Friesen et al 2014). In another study, the data were not reproduced in doxorubicin and MET-treated canine tumor cells (Cueni et al 2020), indicating a need for further in vitro studies. MET has also been implicated in enhancing cytotoxic effects of other chemotherapeutics in cancer cell lines of different origins, such as bladder cancer, squamous cell carcinoma and head and neck cancer, albeit with varying efficacy, greatly depending on cell type, the chemotherapeutic agent and applied concentrations (Landgraf et al 2019;Michalska et al 2018;Shi et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown that MET increases intracellular doxorubicin levels probably by inhibiting P-glycoproteins (P-gp) in GBM cells (Friesen et al 2014). On the other hand, data published by others indicate no sensitizing effect of MET on various doxorubicin-treated canine tumor cells (Cueni et al 2020).…”
Section: Introductionmentioning
confidence: 90%